Pengaruh Kinerja Keuangan terhadap Kebijakan Dividen: Studi pada Perusahaan Manufaktur Sektor Barang dan Konsumsi - Jaya, Asep Sutra; Arnova, Iwin; Riswandi, Pedi (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to determine the impact of financial performance comprising of ROE, CR, and DER on dividend policy measured by DPR. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange during the period 2018-2022 in the Goods and Consumption sector. The sample for this study consisted of 20 companies categorized as manufacturing companies in the Goods and Consumption sector for the period 2018-2022, and companies that were required to issue financial reports containing the values of variables to be examined, namely DPR, ROE, CR, and DER over five consecutive years. The data collection method for this research used secondary sources. Data obtained from the Indonesia Stock Exchange was tested through classical assumption tests including normality test, Autocorrelation Test, Multicollinearity Test, and Heteroskedasticity Test. To answer the hypotheses, multiple linear regression tests were used, hypothesis tests consisting of F-test and t-test, and determination test (R2). The research results indicate that the independent variables, comprising ROE, CR, and DER, have an influence on the dependent variable, which is DPR. The F-test results show that simultaneously, the variables ROE, CR, and DER have a significant impact on DPR. Through the t-test, it was found that the ROE variable has a positive and significant impact on DPR, the CR variable has a positive and significant impact on DPR, and the DER variable has a negative and significant impact on DPR for manufacturing companies listed on the Indonesia Stock Exchange during the period 2018-2022 in the Goods and Consumption sector.